Microtomographic and histologic evaluation of craniofacial reconstructions in rabbits using different biomaterials - Santos, Paula Sanches dos (2020)
The aim was to evaluate the bone formation and bone augmentation in two different models of craniofacial reconstructive surgery using comparatively different calcium phosphate-based ceramics or using deproteinized bovine bone (DBB) in association with angiogenic fraction F1 obtained from latex (Hevea brasiliensis) and hyaluronic acid hydrogel (HAH). In the article 1, bilateral maxillary sinus augmentation (MSA) was performed using carbonated deproteinized bovine bone (cDBB), sinterized deproteinized bovine bone (sDBB) or porous biphasic calcium phosphate (pBCP) in rabbits. After 2, 4 and 8 weeks the samples were collected and analyzed under microtomography, histomorphometry and immunohistochemistry for TRAP labeling. All treatments promoted maintenance of the MSA volume over time. The bone formation occurred in close contact with the surface of all materials particles. In cDBB group the number of TRAP+ cells maintaining stable during all experimental periods, while in sDBB and pBCP groups a peak was observed at 2 weeks. In all experimental periods, bone formation in sDBB group was higher compared to cDBB group and similar to pBCP group. In the article 2, bilateral cranial bone defects were performed and filled with F1/HAH/DBB or HAH/DBB and the contralateral side with F1/HAH or HAH in rabbits. After 2, 4 and 8 weeks the samples were collected to microtomography and histomorphometry analyzes. The total volume (TV) in the HAH/DBB and F1/HAH/DBB groups were significantly higher than in the HAH and F1/HAH groups. At 2 weeks, the F1/HAH/DBB group presented a greater volume bone (BV) compared to the other groups. In HAH/DBB and F1/HAH/DBB groups the bone tissue grew on the surface and pores of the DBB increasing progressively the maturity and the volume occupied. The DBB structure not changed. In defects of the HAH and F1/HAH groups occurred the invasion of the adjacent tegument with formation of a thin layer of connective tissue and small new bone formation limited to the edges during all periods. In conclusion, cDBB, sDBB and pBCP maintained the MSA volume, favoring bone formation and maturation being safe alternatives in the MSA technique. And, the F1 fraction associated to DBB provided significant increase in the bone formation of the cranial bone defects especially at the initial healing phase, suggesting a promising strategy for the treatment of craniomaxillofacial defects.